Statistics for big data for dummies - Anderson, Alan; Semmelroth, David (--For dummies., 2015)
Big data figures into everything from weather forecasting to political polling. You'll get a handle on the statistical methods used when working with big data, applications for it, ways to organize and check data, and a whole lot more. You will find out what big data is, characteristics that define it, how it's used, and what it makes possible; how to handle it by exploring statistical techniques used with big data, including probability distributions, regression analysis, time series analysis, and forecasting techniques; learn how big data can be analyzed with graphical techniques and how to identify valid, useful, and understandable patterns in data; examine key univariate and multivariate statistical techniques for analyzing data; discover techniques for forecasting the future values of a dataset; learn about the best software packages and programming tools for analyzing statistical data. --